Corrigendum to “LightSOD: Towards lightweight and efficient network for salient object detection” [J. Comput. Vis. Imag. Underst. 249 (2024) 104148] (Computer Vision and Image Understanding (2024) 249, (S1077314224002297), (10.1016/j.cviu.2024.104148)) - Ngo, Thu; Tran, Hoang Ngoc; Hossain, Md. Delowar; Huh, Eui Nam (Computer vision and image understanding, 2025)
The authors regret that the corresponding author for this article was incorrectly listed as Ngo Thien Thu (thu.ngo@khu.ac.kr). The correct corresponding author is Eui-nam Huh. Professor Eui-Nam Huh's contact details are as follows: johnhuh@khu.ac.kr Department Computer Science and Engineering, KyungHee University Global Campus, Deogyeong-daero, Yongin-si, 17104, Gyeonggi-do, Republic of Korea The authors would like to apologise for any inconvenience caused. © 2024 The Author(s)